IDENTIFYING LEARNING OBSTACLES OF SEVENTH-GRADE STUDENTS IN QUADRILATERAL TOPICS - Kadir, Kamaliyah; Fatimah, Siti; Darhim, Darhim; Rusli, Andi Zahrah Muflihah (Lembaga Penelitian Mahasiswa Penalaran UNM, 2024)
This study identifies and describes the types of learning obstacles and the factors that cause them in seventh-grade students learning quadrilateral material. The qualitative method used in this research focuses on teaching barriers experienced by students at SMPN 2 Sampit. Data were collected through observation, interviews, written tests, analysis of student answers, and documentation. The results of the study showed that students faced three main types of obstacles, namely ontogeny obstacle (mental readiness, lack of motivation and enthusiasm), didactical obstacle (classical way of teaching and without involving students, less than optimal use of teaching materials using only LKS), and epistemology obstacle (limited context and also low mastery of material owned by students)